2016
DOI: 10.1364/ao.56.000a13
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront sensing by numerical evaluation of diffracted wavefields

Abstract: A novel wavefront sensor principle based on decomposition of the angular spectrum propagator and Fourier analysis is presented. A wavefront is propagated to a 2 dimensional binary cross grating. The appropriate diffraction orders are filtered out and captured by a CCD camera. The following Fourier analysis delivers maps of phase gradients in the x and y coordinates. We verify the presented method by numerical tests and experimentally in a measurement setup on the example of a wavefront generated by a cubic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The main idea of our numerical wavefield analysis is the appropriate decomposition of spherical propagator phase in order to simplify the final Fourier analysis. We perform the numerical propagation in the spectral domain using the angular-spectrum method [7]. The modulated signal is multiplied with the propagation kernel of The phase z is determined by with the spatial…”
Section: Representation Of the Propagator Phasementioning
confidence: 99%
See 1 more Smart Citation
“…The main idea of our numerical wavefield analysis is the appropriate decomposition of spherical propagator phase in order to simplify the final Fourier analysis. We perform the numerical propagation in the spectral domain using the angular-spectrum method [7]. The modulated signal is multiplied with the propagation kernel of The phase z is determined by with the spatial…”
Section: Representation Of the Propagator Phasementioning
confidence: 99%
“…Talbot interferometry is one variation of the interferometric measurements with less sensitivity to environmental noise. In contrast to the conventional interferometry this method does not require a separate beam path for the reference wave simplifying the alignment and reducing the requirements to mechanical stability [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid these challenges, gratings have been suggested as beamsplitters in measurement systems. An example of a system for measuring freeform surfaces which has been suggested by Bichra et al [1,2] is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The 0 th diffraction order is used for illumination, the higher orders are filtered. As the reflected light passes the grating again, just the higher orders carrying the information about the surface are used *Correspondence: julian.wuester@tu-ilmenau.de 1 Department Technical Optics, Institute for Micro-and Nanotechnologies, Technische Universität Ilmenau, 98693 Ilmenau, Germany Full list of author information is available at the end of the article for the detection on the sensor. This allows one to maintain a single optical axis over the whole system.…”
Section: Introductionmentioning
confidence: 99%
“…For a compact in-line measurement system it is necessary to achieve a beamsplitting functionality while maintaining one optical axis over the whole system. This is possible in systems using a diffraction grating as shown in [3] and [4] which uses the O th order for illumination and as the light reflected from the surface-to-be-measured passes the grating again, the higher orders are used for the detection. For this it is advantageous to design a grating, which has low diffraction efficency in the direction of illumination and high efficiency for the reflected light.…”
Section: Introductionmentioning
confidence: 99%